2016
DOI: 10.1002/dneu.22453
|View full text |Cite
|
Sign up to set email alerts
|

Splice form‐dependent regulation of axonal arbor complexity by FMRP

Abstract: The autism-related protein FMRP (Fragile X mental retardation protein) is an RNA binding protein that plays important roles during both nervous system development and experience dependent plasticity. Alternative splicing of the Fmr1 locus gives rise to twelve different FMRP splice forms that differ in the functional and regulatory domains they contain as well as in their expression profile among brain regions and across development. Complete loss of FMRP leads to morphological and functional changes in neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…A recent study has shown that although FMRP is present throughout the brain, its expression varies markedly among different neuronal populations (Zorio et al, 2017). Within a given neuron, FMRP localizes to the soma, developing and mature axons, dendrites, and the base of dendritic spines (Antar et al, 2004(Antar et al, , 2006Ferrari et al, 2007;Zimmer et al, 2017). Because neurons are so highly polarized, transport of mRNAs along the axon and dendrites to undergo local, on-site protein synthesis is key for maintaining proper structural and functional polarity (Bramham, 2008;Cioni et al, 2018;Rangaraju et al, 2017;Tom Dieck et al, 2014).…”
Section: Fmrp At Synapsesmentioning
confidence: 99%
“…A recent study has shown that although FMRP is present throughout the brain, its expression varies markedly among different neuronal populations (Zorio et al, 2017). Within a given neuron, FMRP localizes to the soma, developing and mature axons, dendrites, and the base of dendritic spines (Antar et al, 2004(Antar et al, , 2006Ferrari et al, 2007;Zimmer et al, 2017). Because neurons are so highly polarized, transport of mRNAs along the axon and dendrites to undergo local, on-site protein synthesis is key for maintaining proper structural and functional polarity (Bramham, 2008;Cioni et al, 2018;Rangaraju et al, 2017;Tom Dieck et al, 2014).…”
Section: Fmrp At Synapsesmentioning
confidence: 99%
“…Fragile X mental retardation protein has been implicated as a regulator of synaptic plasticity and thereby learning and memory (reviewed in Bostrom et al, 2016 ). The functions of FMRP in nervous system have been related to the control of synaptic protein synthesis in response to neurotransmitter activation and affecting the formation of axonal and dendritic structures ( Feng et al, 1997 ; Greenough et al, 2001 ; Weiler et al, 2004 ; Zimmer et al, 2017 ). The FMRP-mediated regulation of mRNA translation has been also directly linked to neurotransmitter receptor systems involved in synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies indicate that it is not miRNA alone, but the composition of miRISC has a great significance in the pathophysiology of disorders of the nervous system. There is Bhattacharyya, 2016, 2018) FMRP (Castren et al, 2005;Tervonen et al, 2009;Callan et al, 2010;Saffary and Xie, 2011;Jeon et al, 2014) TRIM-32 (Brat, mei-P26,NHL-2) (Bello, 2006;Betschinger et al, 2006;Lee et al, 2006;Bowman et al, 2008;Neumüller et al, 2008;Hammell et al, 2009;Schwamborn et al, 2009;Loewen et al, 2018) Hu Proteins (Marusich et al, 1994;Dobashi et al, 1998;Kasashima et al, 1999;Anderson et al, 2000;Akamatsu et al, 2002Akamatsu et al, , 2005Perrone-Bizzozero and Bolognani, 2002;Kraushar et al, 2014) Pumilio (Burow et al, 2015;Zahr et al, 2018) ESCRT Factors FMRP (Dockendorff et al, 2002;Ivanco and Greenough, 2002;Morales et al, 2002;Michel, 2004;Pan et al, 2004;Li, 2009;Doll and Broadie, 2015;Wang et al, 2015;Zimmer et al, 2017;Shen et al, 2019) MOV10 (Skariah et al, 2017) Pumilio (Menon et al, 2004(Menon et al, , 2009Ye et al, 2004;Vessey et al, 2010;...…”
Section: Discussionmentioning
confidence: 99%